Extended responsibility or continued dis/articulation? Critical perspectives on electronic waste policies from the Israeli-Palestinian case. (June 2019) - Davis, John-Michael; Garb, Yaakov
Extended producer responsibility policies and interventions propose a template for electronic waste management with considerable and growing discursive and policy traction worldwide. Originating in the global North, they increasingly implicate countries and sites in the global South, in particular, people working in informal electronic waste hubs that process Northern electronic waste. This paper examines the implications of extended producer responsibility in one such place through the lenses of critical waste studies and the dis/articulations approach to global commodity chains, which can usefully be extended to analyze the afterlife of commodities. From Israel and the Palestinian Authority's perspectives, recently activated extended producer responsibility legislation is a common-sense way to rationalize the management of electronic waste. But from the cluster of Palestinian villages that has processed the bulk of Israel's electronic waste for more than a decade, extended producer responsibility constitutes the most recent in a series of external driving forces that have disarticulated and rearticulated their landscapes and livelihoods from external economies over the last half century. The restricted scope of reformist extended producer responsibility policies notion of "responsibility" combined with the asymmetrical terms of dis/articulation between North and South is likely to result in outcomes that not only downgrade the informal sector's position in the value chain, but also undermine their ability to upgrade the electronic waste sector in a way that could avoid further pollution. We consider the options at this junction using the heuristic of suggesting what a more temporally, geographically, and sectorally conceived "extension of responsibility" might mean for extended producer responsibility.